2019
DOI: 10.1136/rapm-2018-100206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient choice for different postcesarean delivery analgesic protocols on opioid consumption: a randomized prospective clinical trial

Abstract: BackgroundChoice of postcesarean delivery analgesic protocol may improve pain experience and reduce analgesic requirements.MethodsCesarean delivery patients were randomly assigned either to choose their postcesarean delivery analgesia protocol or to have no choice and receive routine care. Choices were low (50 μg intrathecal morphine), medium (identical to routine care: 150 μg intrathecal morphine), or high (300 μg intrathecal morphine with 600 mg oral gabapentin). All groups received scheduled acetaminophen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
(14 reference statements)
0
30
0
Order By: Relevance
“…A total of 145 studies were included, of which 126 were randomised controlled trials and 19 were systematic reviews and meta‐analyses (Fig. 1) [9–153]. The methodological quality assessments of the 126 randomised controlled trials included in the final qualitative analysis are summarised in online Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 145 studies were included, of which 126 were randomised controlled trials and 19 were systematic reviews and meta‐analyses (Fig. 1) [9–153]. The methodological quality assessments of the 126 randomised controlled trials included in the final qualitative analysis are summarised in online Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In a comparative study, intrathecal morphine provided better analgesia compared with epidural morphine and patient-controlled epidural analgesia of ropivacaine with sufentanil [44]. In two studies, women were offered to choose the analgesic strategy and select either no intrathecal morphine or a low or high dose of intrathecal morphine [45,46]. Having a choice did not impact on rescue opioid consumption, but women were very good in predicting their actual opioid needs.…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…breastfeeding, caring for their newborn) that differ immensely from the general population. It has been shown that patient choice is an important factor to take into account when tailoring post‐caesarean analgesic approaches [15]. In addition, assessments should continue beyond the immediate surgical period, as adverse outcomes related to poorly controlled pain may arise beyond the usual 72 postoperative hours.…”
Section: Patient Specificmentioning
confidence: 99%